Methodology of integrated survey in process of digital documentation of architectural heritage - Kontic, Ana D; Jadresin- Milic, Renata; Mrljes, Rade (Arhitektura i urbanizam, 2019)
The paper presents an overview of the results based on the integration of traditional (analogue) and instrumental (digital) methods of heritage surveying. The thematic framework was stimulated by participation at the professional workshop in Lizori, in Italy, held in June 2018. This specific methodological framework of integrated research, uses different tools, in the function of morphological specifications of different parts of a historical building. The very nature of architectural heritage requires the integration of different methods in order to achieve an adequate level of accuracy. The project of digitization of the Lizori village aims to present, on the one hand, an almost unknown historical heritage through multimedia presentation, and on the other hand, set up an information tool for restoration, maintenance and valorization.